A articulação de vozes sociais em produções de textos/gêneros do discurso na escola - Batista, Luiz Eduardo Mendes (2023)
In the last years of this century, it has not been difficult to perceive how much we are immersed in language practices in which we are constantly summoned to produce texts, as perhaps never before in human history. The school, as an institution that could more effectively assimilate such practices, in order to enable the enrollment of subject-students in different spheres of circulation, has not yet realized the need for a more engaged social and historical anchorage of the production of texts and has insisted on classificatory and typological approaches. In general terms, this problem encouraged us to take as the central objective of this research to investigate how what we call here as dialogic-discursive competence in textual productions, carried out through the appropriation of discourse genres by subject-students, is constituted. Thus, based on Bakhtin's concepts (2015, 2016), such as discourse genre and heterodiscourse, we could better understand that, by taking discourse genres as an effective teaching object of textual production, it is possible to access social voices and, as an effect of this , to recognize how such dialogic-discursive competence of the subject-students is constituted, so that it is possible to think of ways towards a continuous optimization of this competence. This verification was possible from a data colect of textual productions that we made in a public school in Brasília in 2018, more specifically from an 8th grade class, in which genres had been taken as an object of work with text production. Such collection took place throughout the mentioned year, so that our corpus could count on the production of summaries, carried out at the beginning of the year, and reviews, carried out in the middle and at the end of the school year. Although we have noticed movements of what we call opening, deletion, sedimentation/bricolage, mitigation and silencing of social voices, by the subject-students, it was interesting to notice that, in principle, such movements did not consist of errors or mere misunderstandings committed by the students, but they were part of a broader context of response by these subjects to the production conditions of the school sphere itself. This became clear, for example, in our analysis of the phenomenon of copying. Finally, we proposed, in general lines, a work with what we call reactive genres, in the sense of, inexorably, making social voices emerge in the school that dialogue with the voices of subject-students who produce texts, thus enabling “emancipate intelligences”, in the sense given by Rancière (2017).